Analysis of Tick-borne Encephalitis vaccination coverage and compliance in adults in Switzerland, 2018. Issue 49 (17th November 2020) - Baroutsou, Vasiliki; Zens, Kyra D.; Sinniger, Philipp; Fehr, Jan; Lang, Phung
Highlights: This is the first Switzerland-wide analysis of adult TBE vaccination coverage. Nation wide coverage was 41.7% for 1 dose and 32.9% for a primary series of 3 doses. We estimate that 23% of the population would be protected from the TBEV. TBE vaccination c overage varied widely by region and Swiss canton. Risk perception was most highly correlated with being vaccinated against TBE. We estimate TBE incidence of 6.83 / 100, 000 among unvaccinated adults. Abstract: Background: Overall incidence and geographic range of Tick-borne Encephalitis (TBE), a vaccine preventable infection, have steadily increased in Switzerland over the last 50 years. While fully subsidized vaccination has been recommended in many areas for well over a decade, vaccine coverage and variables associated with vaccination compliance among Swiss adults are poorly understood. Methods: In 2018 we conducted a national, cross-sectional survey of vaccination cards evaluating TBE vaccination coverage and compliance among adults (18-79) in Switzerland. Results: Nationwide TBE vaccination coverage was 41.7% (range 14.3% to 60.3%) for 1 dose and 32.9% (range 8.4% to 50.4%) for a complete primary series (3 doses). There was a significant correlation between average disease incidence by canton (2009-2018) and vaccine coverage at both 1 and 3 doses. Of the overall population, 9.5% had received at least one TBE booster vaccination with large regional coverage variation. We estimated that 23% of adults in Switzerland would be protected from infection based on their vaccination history and 135 (95% CI: 112-162) TBE cases were prevented in 2018. Individuals reporting previous experience with tick-associated health problems, those frequently in nature or those with "high" perceived risk of contracting TBE, were significantly more likely to have received at least one vaccine dose, indicating a positive impact of awareness on vaccination compliance. We also calculated a TBE incidence rate of 6.83/100, 000 among the unvaccinated adult population in Switzerland and estimated vaccine effectiveness at 91.5% (95% CI: 90.9-92.0%). Conclusions: These findings provide an important reference for TBE vaccination levels in Switzerland and further suggest that public health interventions promoting knowledge of TBE health impacts and risk factors may be beneficial in improving TBE vaccination coverage but should be tailored to account for heterogeneity in vaccine uptake.